Reliability, validity and applicability of isolated and combined sport-specific tests of conditioning capacities in top-level junior water polo athletes - Uljevic, O.; Esco, M. R.; Sekulic, D. (The Journal of Strength and Conditioning Research, 2014)
Standard testing procedures are of limited applicability in water sports, such as water polo. The aim of this investigation was to construct and validate methods for determining water polo-specific conditioning capacities. We constructed 4 combined-capacity tests that were designed to mimic real-game water polo performances: sprint swimming performance, shooting performance, jumping performance, and precision performance. In all cases, combined-capacity tests included a period of standardized exhaustion followed by the performance of the targeted quality (swimming, shooting, jumping, and precision). In the first part of the study, single-capacity tests (sprint swim, in-water jump, drive shoot, and precision performance) were tested and later included in the combined-capacity tests. Study subjects consisted of 54 young male water polo players (15-18 years of age, 185.6 ± 6.7 cm, and 83.1 ± 9.9 kg). Most of the tests evaluated were found to be reliable with Cronbach alpha values ranging from 0.83 to 0.96 and coefficients of variation from 21 to 2% (for the single-capacity tests) and 0.75 to 0.93 test-retest correlation (intraclass correlation coefficients) with Bland-Altman tight limits of agreement (for combined-capacity tests). The combined-capacity tests discriminated qualitative groups of junior water polo players (national squad vs. team athletes) more effectively than single-capacity tests. This is most likely because combined-capacity tests more closely represent the complex fitness capacities required in real game situations. Strength and conditioning practitioners and coaches working with water polo athletes should consider incorporating these validated tests into their assessment protocols.